Affective orientations of perpetrators, victims, and functional spouses - Yelsma, P. (Journal of interpersonal violence, 1996)
Affective orientations of 79 perpetrators, 57 victims, and 70 functional spouses were examined. Self-report measures were utilized to assess five affective orientations: (a) alexithymia, (b) affective orientation, (c) range of positive feelings, and (d) expression of positive affect, and (e) expression of negative affect. Perpetrators were significantly more alexithymic than functional spouses but were not significantly different from victims. Perpetrators and victims report being less disposed to possess or express their feelings than do functional males and females. Male perpetrators were significantly less aware of their affective states than functional males; and female victims were significantly less aware of their affective states than functional females. Female victims possessed significantly fewer positive feelings than functional women. Expression of positive emotions was significantly less for female victims than for functional females. Deficit of positive affect versus the presence of negative affect was a significant indicator of physical abuse reported within intimate relationships